Những nhân tố xác định sự hữu hiệu của các tổ chức ứng dụng hệ thống hoạch định nguồn lực doanh nghiệp tại Việt Nam - Nguyễn Việt; Vũ Quốc Thông (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This paper explores factors that define the effectiveness of business organization that has applied ERP system. The survey data comprise 316 businesses operating in Vietnam that contain ERP systems usage. Correraltion analysis, descriptive statistics, and exploratory factor analysis (EFA) are used to validate and interpret the BSC-based resarch model. The results indicate that there are three groups of second-order constructs, including business stable development, organizational capability, and readiness in business, which determine ERP-applied organizational effectiveness. Each second-order construct is defined by a set of first-order constructs and related observed variables. The research value falls in a position that partly satisfies the measurement demand of business managers for the concept of ERP-applied organizational effectiveness.
Keywords: Organizational Effectiveness; the Value of IS; ERP-applied